Introducing globalization : Ties, Tension, and Uneven Integration - Sparke, Matthew (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
'Introducing Globalization is a major textbook on globalization designed specifically for introductory courses, actively encouraging students to engage with the topic and develop informed opinions about controversial debates'--
Includes bibliographical references and index.
Keywords: International economic integration; Globalization; POLITICAL SCIENCE / Globalization